A sensitive, uniform, reproducible and stable SERS substrate has been presented based on MoS2@Ag nanoparticles@pyramidal silicon. Issue 10 (18th January 2017) - Jiang, Shouzhen; Guo, Jia; Zhang, Chao; Li, Chonghui; Wang, Minghong; Li, Zhen; Gao, Saisai; Chen, Peixi; Si, Haipeng; Xu, Shicai
Abstract : By combine the Ag nanoparticles, pyramidal silicon and molybdenum disulfide, the MoS2 @AgNPs@PSi substrate shows high performance in terms of sensitivity, uniformity, reproducibility and stability. Abstract : By combining the excellent surface-enhanced Raman scattering (SERS) activity of Ag nanoparticles (AgNPs), the well-separated pyramid arrays of the pyramidal silicon (PSi) and unique physical/chemical properties of molybdenum disulfide (MoS2 ), the MoS2 @AgNPs@PSi substrate shows high performance in terms of sensitivity, uniformity, reproducibility and stability. By using rhodamine 6G (R6G) as probe molecule, the SERS results indicate that the MoS2 @AgNPs@PSi substrate is superior to the AgNPs@PSi, AgA@PSi (the second annealing of the AgNPs@PSi) and the MoS2 @AgNPs@flat-Si substrate. The MoS2 @AgNPs@PSi substrate also shows the reasonable linear response between the Raman intensity and R6G concentration. The maximum deviations of SERS intensities from 20 positions on a same MoS2 @AgNPs@PSi substrate and 10 MoS2 @AgNPs@PSi substrates in different batches are less than 7.6% and 9%, respectively, revealing the excellent uniformity and reproducibility of the substrate. Besides, the SERS substrate has a good stability, the Raman intensity of the MoS2 @AgNPs@PSi substrate only drop by 15% in a month. The corresponding experimental and theoretical results suggest that our proposed MoS2 @AgNPs@PSi substrate is expected to offer a new and practical way to accelerate the development of label-free SERS detection.